2014
DOI: 10.2116/analsci.30.805
|View full text |Cite
|
Sign up to set email alerts
|

Ligation-Independent Mechanism of Multiplex Ligation-Dependent Probe Amplification

Abstract: Multiplex ligation-dependent probe amplification (MLPA) is a widely used technique for detecting genomic structural variants. The technique is based on hybridization and ligation, followed by amplification of the ligation products. Therefore, ligation is considered a fundamental process that determines the feasibility and fidelity of MLPA. However, despite the widespread use of this technique, its reaction mechanism has not been fully analyzed. Herein, we describe a ligation-independent pathway for MLPA and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…targets with a single primer pair Thomas et al., 2010a;Uno and Yanagihara, 2014). This system provides several advantages compared to real-time PCR.…”
Section: Insect Sample Preparation and Pathogen Scanningmentioning
confidence: 99%
“…targets with a single primer pair Thomas et al., 2010a;Uno and Yanagihara, 2014). This system provides several advantages compared to real-time PCR.…”
Section: Insect Sample Preparation and Pathogen Scanningmentioning
confidence: 99%
“…We previously uncovered a ligation-independent pathway of MLPA through which products of MLPA could be amplified without hybridization and ligation processes (Uno and Yanagihara, 2014). The ligation-independent pathway led to notable levels of amplification.…”
mentioning
confidence: 99%
“…When the mutation is present, amplification is refractory because of a mismatch between the 3′ end of the left probe and the template. We previously showed that ligation-independent probe amplification could not distinguish the point mutation in oligonucleotide templates (Uno and Yanagihara, 2014), but we tried to increase its fidelity by optimizing PCR conditions. We designed an additional probe pair targeting N-acetylmuramoyl-L-alanine amidase (lytA), which is commonly present in S. pneumoniae (Sheppard et al, 2004), to confirm the presence of the bacterium.…”
mentioning
confidence: 99%